The Effect of Change Perceptions in Price, Service Quality and Brand Image on Consumer Shopping Behavior During the COVID-19 Pandemic - Nur Edi Nomalisa; Anggrieni Wisni (Journal Research of Social Science, Economics, and Management, 2022)
The COVID-19 pandemic is forcing the world community to adopt new habits, one of the new habits at once The solution is Gojek as an online delivery service. This research aims to understand the effect of changes in consumer perceptions in terms of price, quality and brand image on consumer shopping behavior during the COVID-19 pandemic. The type of research used is explanatory research, with a quantitative approach. The research subjects are Go-food customers in Yogyakarta during the COVID-19 pandemic and the objects of research are consumer perceptions, prices, service quality, brand image and consumer shopping behavior. and customer satisfaction. Data collection techniques were carried out through questionnaires and documentation which were analyzed using multiple linear regression. The results showed that consumer perceptions in terms of price, service quality, and brand image had a significant positive effect on consumer shopping behavior during the COVID-19 pandemic.